ESENSI SUMBER DAYA MANUSIA - Taufik Akhyar (Wardah, 2013)
Modern management perspective , is positioned as a human resources (resources) are major and important within an organization as compared to other resources . H.Malayu SPHasibuan explains that humans are always active and dominant role in any organization's activities , as humans become planners , perpetrators and decisive realization of organizational goals . The goal is not possible without the active role even though the employee -owned devices are so sophisticated organizations . Advanced tools of the organization there will be no benefit to the organization , if the active role of the organization is not included . Set up employees as humans is difficult and complex , because they have thoughts , feelings , status , desire , and heterogeneous backgrounds they bring in the organization . Employees can not be regulated and controlled entirely as set machinery , capital , or building . Managing humans, especially in public organizations requires knowledge and a deep understanding of its essence . In several studies that there is a description of the essence of man is still very shallow , both in terms of psychological , sociological , and anthropological.